Aspects of ancient near Eastern calendars : a study of month names from southern Mesopotamia, Ebla and Mari - Van Wyk, Koot Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1989.